Analisis Penerapan PSAK 71 terhadap Pencadangan Piutang pada Perbankan - Carmanita Aisyah Pandanwangi; Arik Susbiyani; Elok Fitriya (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to determine the analysis of PSAK 71 on the provision of receivables at banks in Indonesia. The data in this study used qualitative methods in the form of secondary data and information on financial statements of banking companies registered in Indonesia. The sample in this study was selected with the criteria of being a banking company listed on the Indonesia Stock Exchange (IDX) based on the number of assets in 2019. The sample in this study was six 6 banking companies. Based on the results of the analysis and discussion, it shows that companies in the banking sub-sector are ready to apply PSAK 71 (2017). In addition, the results of this study explain that the application of PSAK 71 has an impact on capital in each company.